Multimodal endovascular management of traumatic carotid-cavernous fistulas: case series and lessons learned - Yang, Shangdi; Chen, Richao; Yi, Mingjia; Li, Chuangnan (Frontiers in Pharmacology, 2025)
IntroductionTraumatic carotid-cavernous fistulas (CCFs) are rare but potentially life-threatening vascular anomalies resulting from head trauma. Oxidative stress markedly disrupts resolution and vascular function, significantly hindering recovery.MethodsThis study presents a case series of six patients diagnosed with CCFs following traumatic events. The cases highlight the complexity of clinical presentation, imaging findings, and treatment approaches, emphasizing the role of advanced endovascular techniques in managing these conditions.ResultsPatients underwent a combination of coil embolization, stent-assisted embolization, and balloon-assisted occlusion, demonstrating the necessity of personalized multimodal treatment strategies. Postoperative outcomes varied, with most patients achieving fistula closure and symptom stabilization, although visual impairments persisted in some cases.ConclusionThis study highlights the importance of prompt diagnosis, interdisciplinary collaboration, and personalized evolving endovascular interventions in optimizing patient outcomes in traumatic CCFs.